2007
DOI: 10.1155/2007/59676
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety from a Phylogenetic Perspective: Is there a Qualitative Difference between Human and Animal Anxiety?

Abstract: A phylogenetic approach to anxiety is proposed. The different facets of human anxiety and their presence at different levels of the phylum are examined. All organisms, including unicellular such as protozoan, can display a specific reaction to danger. The mechanisms enabling the appraisal of harmful stimuli are fully present in insects. In higher invertebrates, fear is associated with a specific physiological response. In mammals, anxiety is accompanied by specific cognitive responses. The expression of emotio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 163 publications
(159 reference statements)
2
42
0
2
Order By: Relevance
“…Such behavior is also referred to as thigmotaxis. This pattern of behavior is also consistent with previous findings in rodents [7][8][9]35] thus confirming that an unfamiliar environment can robustly evoke anxiety-like behavioral responses such as thigmotaxis in zebrafish. However, pharmacological manipulations using anti-anxiety drugs remain to be performed to ascertain the anxiety-like nature of darkavoidance (in the light/dark box) and thigmotaxic (in the open field) behaviors in zebrafish.…”
Section: Avoidance Behaviorssupporting
confidence: 91%
See 2 more Smart Citations
“…Such behavior is also referred to as thigmotaxis. This pattern of behavior is also consistent with previous findings in rodents [7][8][9]35] thus confirming that an unfamiliar environment can robustly evoke anxiety-like behavioral responses such as thigmotaxis in zebrafish. However, pharmacological manipulations using anti-anxiety drugs remain to be performed to ascertain the anxiety-like nature of darkavoidance (in the light/dark box) and thigmotaxic (in the open field) behaviors in zebrafish.…”
Section: Avoidance Behaviorssupporting
confidence: 91%
“…After correcting for arena size, we also observed that stressed (but not non-stressed control) zebrafish no longer display any preference for either inner or outer zones. Traditionally, increased time and exploration of aversive zones in both light/dark box [32,33] and open field [8,9,31,35,47] tests in rodents are usually regarded as anxiolytic effects. These findings therefore suggest that acute stress may momentarily relieve anxiety in zebrafish.…”
Section: The Impact Of Prior Acute Stress Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…However, emotions such as fear and anger, which underlie anxiety and depression, may, indeed, be there. Interesting, the potential for fruit flies to be used to study anxiety and depression has been stated several times (Belzung & Philippot, 2007;Damasio, 2001;Kalueff et al, 2007;Moldin, 2000). To date, Drosophila has been successfully used as a model system to elucidate molecular, physiological, and behavioral mechanisms of several human neurodegenerative diseases, including Alzheimer's, Parkinson's, and Huntington's (Chan & Bonini, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…When stress is prolonged, it can elicit long-lasting behavioral adaptations, resulting in a sustained apprehension of the environment, which persists even in a new context and in the absence of stressor. This state of higher alertness is called anxiety (Blanchard and Blanchard, 1988;Belzung and Philippot, 2007;Steimer, 2011). Recently, it has been shown that anxiety-like behavior (ALB) is also observable in crustaceans (Fossat et al, 2014), allowing the study of primitive forms of anxiety and of their neurobiological correlates.…”
Section: Introductionmentioning
confidence: 99%